1976
DOI: 10.1111/j.1600-0447.1976.tb00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Treatment and Weight Gain

Abstract: The problem of lithium maintenance treatment and weight gain was examined in 70 manic-melancholic patients who had been in treatment for 2 to 10 years. Their case records were reviewed and they answered a questionnaire. Out of 70 patients, 45 increased in weight with a mean weight gain of about 10 kg. The patients who increased in weight during the treatment were overweight already before the start and reached a weight about 20% higher than their ideal weight. They nearly all found themselves overweight and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
3

Year Published

1978
1978
2014
2014

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(36 citation statements)
references
References 14 publications
1
32
0
3
Order By: Relevance
“…The "carbohydrate craving" that is thought to be one of the mechanisms of increased calorie intake in people taking lithium is well known. 36 However, reports suggest that valproate also stimulates weight gain through a variety of mechanisms. 37 Of all the patient groups taking psychotropic drugs, patients with schizophrenia tend to be the most studied group and thus the group for which the greatest amount of information is available.…”
Section: Treatments For Psychiatric Disorders Exacerbate Metabolic Symentioning
confidence: 99%
“…The "carbohydrate craving" that is thought to be one of the mechanisms of increased calorie intake in people taking lithium is well known. 36 However, reports suggest that valproate also stimulates weight gain through a variety of mechanisms. 37 Of all the patient groups taking psychotropic drugs, patients with schizophrenia tend to be the most studied group and thus the group for which the greatest amount of information is available.…”
Section: Treatments For Psychiatric Disorders Exacerbate Metabolic Symentioning
confidence: 99%
“…We have previously tested for unwanted effects during long-term lithium treatment both in manic-melancholic patients and in patients without psychiatric disorders (Beck et al, 1976a, b;Vendsborg et al, 1976). We found that lithium induced hand tremor, thirst or polyuria and weight gain, but no unwanted effect associated with cognitive or psychomotor functions, including skills related to driving.…”
Section: Introductionmentioning
confidence: 99%
“…Medication seems to have a signifi cant impact (McIntyre 2002 ;Keck and McElroy 2003 ). Lithium (Vendsborg et al 1976 ;Sachs et al 2006 ) and valproate (Dinesen et al 1984 ;Pylvanen et al 2002 ;Swann 2001 ) can cause weight gain. It has been reported that patients on lithium gain weight in contrast to patients under lamotrigine Muller-Oerlinghausen et al 1979 ;Atmaca et al 2002 ;Vendsborg et al 1976 ) and weight gain during lithium treatment has shown to lead to poor adherence (Gitlin et al 1989 ).…”
Section: Obesitymentioning
confidence: 98%
“…Lithium (Vendsborg et al 1976 ;Sachs et al 2006 ) and valproate (Dinesen et al 1984 ;Pylvanen et al 2002 ;Swann 2001 ) can cause weight gain. It has been reported that patients on lithium gain weight in contrast to patients under lamotrigine Muller-Oerlinghausen et al 1979 ;Atmaca et al 2002 ;Vendsborg et al 1976 ) and weight gain during lithium treatment has shown to lead to poor adherence (Gitlin et al 1989 ). Treatment with antipsychotics and especially with those belonging to the second generation has also been related to weight gain (Henderson et al 2000 ;Simpson 2005 ;Volavka et al 2002 ;Zipursky et al 2005 ;Nasrallah 2003 ).…”
Section: Obesitymentioning
confidence: 99%